ILMU PENDIDIKAN DI INDONESIA DALAM PERSPEKTIF FILSAFAT ILMU - Mia Azzahra; Muhammad Nurwahidin; Sudjarwo, Sudjarwo (Journal of Innovation Research and Knowledge, 2022)
Science of education is a form of scientific thought so that it is seen as an important branch of science, including in Indonesia. Science of education is divided into three classifications, science of education, praxeology of education, philosophy of education. This study uses a systematic literature review method. The search for articles collected by researchers through the Google Scholar database, and Garuda, which then obtained 16 articles as the final result after going through the screening stage. This study aims to review the science of education in Indonesia using perspective of the philosophy of science. This study outcome shows that, if viewed from a philosophical perspective, the philosophy of science is seen as having a position which can be used as a reference to build a paradigm of education in Indonesia.